EV-microRNA signatures in pregnant women with idiopathic recurrent pregnancy loss: deciphering microRNAome pathway networks at feto-maternal interface - Bhardwaj, Chitra; Rohilla, Minakshi; Chopra, Seema; Kaur, Anupriya; Panigrahi, Inusha; Srivastava, Priyanka (Frontiers in Immunology, 2025)
BackgroundDespite extensive research in the past decade, the exact pathogenesis of recurrent pregnancy loss (RPL) remains unknown. At the time of pregnancy, human placenta releases microRNAs (miRNAs) enclosed in extracellular vesicles (EVs), which enter into maternal circulation and play an important role at feto-maternal interface to sustain a successful pregnancy. Aberrant expression of these miRNAs often results in adverse pregnancy complications. Therefore, studying the expression of these EV-miRNAs in maternal circulation could provide insights into the pathogenesis of RPL.MethodsThe present study included idiopathic currently pregnant (<22 weeks of gestation) RPL women (n=10) and gestational-age-matched healthy pregnant women as control (n=5). EVs were isolated from plasma samples and characterized for their morphology and cell-surface marker. Total RNA was isolated and subjected to miRNA sequencing on Illumina NovaSeq 6000 platform. Differentially expressed (DE) miRNAs were identified using DESeq package. Target prediction and pathway analysis were done using TargetScan, miRDB, miRTarBase, and DIANA-miRPath v3.0 online tool. Protein–protein interaction was done using STRING, and hub genes were identified using Cytoscape software.ResultsmiRNA sequencing revealed 66 (44 known and 22 novel) significantly DE miRNAs between RPL and healthy pregnant women. Among these, 37 were downregulated and 29 were upregulated, log2|FC| ≥ 1. Network-based analysis showed highest degree for nine miRNAs (hsa-miR-155-5p, hsa-miR-26a-5p, hsa-miR-204-5p, hsa-miR-140-5p, hsa-miR-139-5p, hsa-let-7e-5p, hsa-miR-149-5p, hsa-miR-374a-5p, and hsa-miR-190a-5p). Gene Ontology (GO) and KEGG pathway analysis of target genes showed significant involvement of Hippo, FoxO, TGF-β, and p53 signaling pathways, which play a crucial role in RPL. Top 10 identified hub genes (NFKB1, IL6, JUN, FOS, CXCL8, PTGS2, TGFB1, MMP9, STAT1, and CD4) were significantly enriched in immunological pathways—Th1/Th2/Th17 differentiation, NF-κB pathway, TNF-α signaling, IL-17 signaling pathway, and vascular endothelial growth factor (VEGF) pathway.ConclusionThese results suggest that circulating EV-miRNAs in maternal blood could provide clinical insights into the pathogenesis of RPL and dysregulated immunological and molecular pathways at feto-maternal interface.